Celastrol Inhibits Dopaminergic Neuronal Death of Parkinson's Disease through Activating Mitophagy - Ming-Wei Lin; Chi Chien Lin; Yi-Hung Chen; Han-Bin Yang; Shih-Ya Hung (MDPI AG, 2019)
Parkinson’s disease (PD) is a neurodegenerative disease, which is associated with mitochondrial dysfunction and abnormal protein accumulation. No treatment can stop or slow PD. Autophagy inhibits neuronal death by removing damaged mitochondria and abnormal protein aggregations. Celastrol is a triterpene with antioxidant and anti-inflammatory effects. Up until now, no reports have shown that celastrol improves PD motor symptoms. In this study, we used PD cell and mouse models to evaluate the therapeutic efficacy and mechanism of celastrol. In the substantia nigra, we found lower levels of autophagic activity in patients with sporadic PD as compared to healthy controls. In neurons, celastrol enhances autophagy, autophagosome biogenesis (Beclin 1↑, Ambra1↑, Vps34↑, Atg7↑, Atg12↑, and LC3-II↑), and mitophagy (PINK1↑, DJ-1↑, and LRRK2↓), and these might be associated with MPAK signaling pathways. In the PD cell model, celastrol reduces MPP+-induced dopaminergic neuronal death, mitochondrial membrane depolarization, and ATP reduction. In the PD mouse model, celastrol suppresses motor symptoms and neurodegeneration in the substantia nigra and striatum and enhances mitophagy (PINK1↑ and DJ-1↑) in the striatum. Using MPP+ to induce mitochondrial damage in neurons, we found celastrol controls mitochondrial quality by sequestering impaired mitochondria into autophagosomes for degradation. This is the first report to show that celastrol exerts neuroprotection in PD by activating mitophagy to degrade impaired mitochondria and further inhibit dopaminergic neuronal apoptosis. Celastrol may help to prevent and treat PD.